Addenda Orchidaceis Quepoanis - Pupulin, Franco (Universidad de Costa Rica, 2016)
Sixteen orchid species are first reported for the area of Quepos in addition to those recorded for Manuel Antonio National Park, Costa Rica. Generic descriptions are provided for the genera not previously recorded for the area, and each species is described and illustrated. Data on distribution and phenology are provided, together with keys to the genera including more than one species in the area. A new species, Epidendrum montis-narae Pupulin & L.Sánchez, is decribed and illustrated. Two previously recorded species, Epidendrum isomerum and Oncidium polycladium, are illistrated from material collected within the study area.